Paciente femenina de 48 años de edad con cirrosis hepática. - Mosquera Carpio, Katherine Betzabe (2021)
The present clinical case is based on a 48-year-old female patient with a diagnosis of Hepatic Cirrhosis, who comes to the health facility for presenting a clinical picture of abdominal pain valued at eight out of ten, non-quantified hyperthermia and melena more than five occasions a day. She is attended in a nutritional consultation whose objective is to provide nutritional support that contributes to improving the state of health, through a correct assessment and diagnosis, and nutritional intervention by providing the patient, a DIETOTHERAPEUTIC PLAN AND NUTRITIONAL COUNSELING that protects her nutritional status and reduces complications of the disease. During the nutritional assessment, the patient was found to be overweight, with insufficient food intake (1500 calories), anemia, hypoproteinemia, and hypoalbuminemia. A dietary plan of 1800 calories necessary to meet their current requirements, control their complications, was proposed. In addition to adequate monitoring and follow-up of their nutritional clinical status.